Diversity Hotspots and Vulnerability of Pine Species in the Sierra Madre Occidental, Western Mexico - Lizeth Ruacho‐González; José Javier Corral‐Rivas; Jesús Guadalupe González‐Gallegos; M. Socorro González‐Elizondo; Pablito Marcelo López‐Serrano; Jaime Briseño‐Reyes (Ecology and Evolution)
ABSTRACT Mexico is a global hotspot for pine diversity, with approximately 60 taxa mainly found in temperate mountainous areas. For this reason, they face increasing threats from climate change, particularly within the Sierra Madre Occidental (SMO). This study aimed to identify areas with the highest potential pine richness in SMO and determine which species are at risk, using current and future potential distribution models. The distribution of 19 pine species was modeled based on 7020 records. Environmental variables were carefully selected from WorldClim 2.1, by multicollinearity elimination and then selecting those with a strong correlation to species presence (Spearman's coefficient ρ > 0.70). Models were developed in MaxEnt using the GISS E2‐1‐G model to predict future distributions in the “245” Shared Socioeconomic Pathway in a “middle of the road” scenario for 2040, 2060, 2080, and 2100. The resulting species‐specific models were overlayed to identify areas most suitable to host the greatest number of species across all projections. Results indicate that the areas with environmental characteristics to host the highest number of pine species are located on the upper portions of the SMO's western slopes. Models indicate a general trend of decreasing pine distribution area in the region; with estimated reductions ranging from 22% to 29% for Pinus durangensis, P. devoniana, and P. engelmannii. The worst situation is for P. brachyptera which may practically disappear by 2060. Despite habitat reductions, species such as P. cembroides, P. devoniana, and P. oocarpa show a tendency to migrate to higher altitudes. The principal conclusions are: pine species hotspot areas are situated on the SMO's western slopes in Durango state, just above the Tropic of Cancer. Approximately 95% of the studied pine species in SMO will show reductions by the end of the century, and P. brachyptera is at risk of extirpation in Mexico.